Perioperative immune checkpoint inhibitors in elderly patients with resectable NSCLC: a systematic review and meta-analysis - Cao, Yue; Tian, Yumeng; Li, Lin (Frontiers in Oncology, 2025)
BackgroundPerioperative immunotherapy has shown promising results in patients with resectable stage II-III non-small cell lung cancer (NSCLC). However, its benefits for the specific subgroup of elderly patients remain unclear. This study aims to evaluate the efficacy of perioperative immunotherapy in elderly NSCLC patients aged 65 and above, focusing on key metrics such as pathological complete response (pCR), event-free survival (EFS), and overall survival (OS).MethodsWe conducted a comprehensive meta-analysis of randomized clinical trials that reported subgroup data on elderly patients regarding pCR rates and hazard ratios (HRs) for EFS and OS. Data were retrieved from PubMed, EMBASE, and proceedings of oncology conferences from January 2020 to June 2025.A fixed effects model was used for the meta-analysis. Aggregated pooled HRs for time-to-event outcomes (EFS and OS), odds ratios (OR) and risk ratios (RRs) for dichotomous outcomes (pCR) were calculated specifically for patients aged ≥65 years who received perioperative immunotherapy or placebo.ResultsA total of 8 randomized controlled trials involving 1561 patients aged ≥65 years with resectable NSCLC were included. A significant benefit was observed in terms of pCR (risk ratio, 5.26; 95% CI, 3.54 – 7.82; I² = 0%) and EFS (HR, 0.64; 95% CI, 0.55 – 0.74; I² = 7%) for patients aged ≥65 years who received perioperative immunotherapy compared with placebo.ConclusionOur systematic review and meta-analysis demonstrated that perioperative immunotherapy was superior to placebo in terms of pathological and event-free survival for patients aged ≥65 years. These findings provide age-specific evidence to inform precision decision-making for treating the elderly patients.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420250654072.